Estrategias de afrontamiento y percepción de la enfermedad en padres de nifios con enfermedad crónica: contexto del cuidador (2009)
The study evaluated the relation between illness perception and coping strategies used by parents/caretakers of children with chronic illness. The participants were the 40 participants identified in the available services in the town of Canoas/RS in 2007, April to May. As instruments, were used the Inventory of Coping Strategies, Illness Perception Questionnaire (IPQ-R) adapted for the parents/caretaker and a partner-demographic Questionnaire developed for the study. The mothers constituted to majority of the caretaker. The results showed the perception of worse consequences of the illness associates-itself to a higher utilization of the coping strategy of escape- avoidance, whereas a lower utilization of that same strategy relates-itself to more clarity about the symptoms.